A PROPOSED FINDING AID FOR THE CULION RECORDS HELD IN THE JESUIT ARCHIVES - Chua, Raymund Melvin S. (Journal of Philippine Librarianship; Vol 27, No 1&2 (2007), 2008)
The Island of Culion in Northern Palawan served as among the world’s largest leprosariums since its establishment by the American-sponsored Insular Government in 1906. It was created mainly for the segregation of people affected by leprosy given the absence of a cure for the disease. With the development of the Multi Drug Therapy (MDT), modern medicine eventually declared a victorious stance against leprosy thus eliminating it in Culion. In the quest to document and preserve the very few written sources of leprosy in the country, a movement to inventory the remaining documentary evidence of leprosy in Culion began. Three main sources of leprosy records in Culion were identified, namely: the municipal office, hospital records and the church archives. Through the years, records of the Church in Culion were lost, mainly attributed to various natural incidents. Thus the documents of the activities of a religious order that cared for the patients in the colony, the Society of Jesus, were practically obliterated. The Jesuits served as colony chaplains throughout the existence of Culion as a leprosarium and their documents pose as a valuable trove of resources to the island’s past. Fortunately, records on Culion still exist at the Jesuit Archives based in Metro Manila. With the goal of providing access to materials that would complement the lost records and highlight the activities and writing of the Jesuits, this study has focused on developing a finding aid to the Jesuit Records of Culion (dated 1904– 1941) housed in the Archives of the Philippine Province, Loyola House of Studies, Ateneo de Manila University. Constructing the finding aid involved archival arrangement and description, using the General International Standard Archival Description or ISAD(g), Second Edition, 2000, and all the Jesuit Papers about Culion were considered a manuscript collection and called “The Culion Papers”. The collection was dominated by correspondence and it was difficult to assign particular contexts of creation that would be the basis of the series arrangement. With only the chronological arrangement of papers, analysis by provenance, or granting attribution to the creating body, proved to be a challenging process. By treating documents as “products of work processes” and “multicontextual traces of action”, along with the principles enshrined in ISAD(g), the context of creation of each item (document) was determined. An expanded and detailed document analysis judged each document based on the presentation of information, the objective/motive of the person/creator and the content. Historical Research into the Corporate Nature of the Society, Jesuit Reportage and Information Mechanism/System was necessary to see their administrative context. The constructed finding aid consisted of five series which are the recordmaking activities of the Jesuits in Culion, namely: correspondence, calling for donors and donations, producing mission reports, adhering to binding documents (case files) and publishing materials about their work. Correspondence involved government relations, communication with superiors, Church building and repair, assets or business ventures and personal communications. The act of formal reportage involved producing narratives of the mission, writing the Jesuit classics of Litterae Annuae and Historia Domus, reporting finances through Status Temporalis and religious services through statistics. The effective correspondence network distinct to the Order ensured the regularity of Jesuit communication from their missions. Corporate Nature, training and education of its members guaranteed a style of writing that is scientific and concise in elements.
Keywords: Jesuits--Archives, Leprosarium--Records--Culion (Northern Palawan, Philippines)